Sex discrepancies in COPD patients and burden of the disease in females: a nationwide study in Greece (Greek Obstructive Lung Disease Epidemiology and health ecoNomics: GOLDEN study) - Papaioannou, Andriana I (Dove Medical Press, 2014)
BACKGROUND: The prevalence of chronic obstructive pulmonary disease (COPD) in females appears to be increasing. Recent studies have revealed that the percentage of women with COPD in Greece is approximately 12.5%. AIMS: To evaluate the burden of COPD among males and females in Greece through a nationwide cross-sectional survey and to explore sex differences regarding functional characteristics and exacerbation frequency. METHODS: Data collection was completed in a 6-month period. The present study followed a nationwide sampling approach of respiratory medicine physicians. The sampling approach included three steps: 1) estimation of expected incidence and prevalence of COPD cases in each prefecture of Greece and in total; 2) estimation of expected incidence of COPD cases per physician in each prefecture; and 3) creation of a frame of three different sampling zones. Following this sampling, data were provided by 199 respiratory physicians. RESULTS: The participating physicians provided data from 6,125 COPD patients. Female patients represented 28.7% of the study participants. Female COPD patients were, on average, 5 years younger than male COPD patients. Never smokers accounted for 9.4% within female patients, compared to 2.7% of males (P<0.001). Female patients were characterized by milder forms of the disease. Comorbidities were more prevalent in men, with the exception of gastroesophageal reflux (14.6% versus 17.1% for men and women, respectively, P=0.013). Female COPD patients had a higher expected number of outpatient visits per year (by 8.9%) than males (P<0.001), although hospital admissions did not differ significantly between sexes (P=0.116). Females had fewer absences from work due to COPD per year, by 19.0% (P<0.001), compared to males. CONCLUSION: The differences observed between male and female COPD patients provide valuable information which could aid the prevention and management of COPD in Greece.